2015
DOI: 10.2147/ndt.s65735
|View full text |Cite
|
Sign up to set email alerts
|

Profile of guanfacine extended release and its potential in the treatment of attention-deficit hyperactivity disorder

Abstract: The α2-adrenergic receptor agonist guanfacine, in its extended-release formulation (GXR), is the most recent nonstimulant medication approved in several countries for the treatment of attention-deficit hyperactivity disorder (ADHD) as monotherapy and as adjunctive pharmacotherapy to stimulants in children and adolescents. The present paper aims to review comprehensively and critically the pharmacodynamic and pharmacokinetic characteristics and the published evidence on the efficacy and safety profile of GXR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…While, atomoxetine overall is less likely than stimulants to worsen sleep problems, initial somnolence can be observed, particularly if the dosage is increased too rapidly [Wolraich et al 2007]; however insomnia may also be experienced by adult patients taking atomoxetine [Wietecha et al 2013]. Likewise, the most common TEAEs associated with the α2-adrenergic receptor agonists guanfacine-XR (GXR) and clonidine-XR (CLON-XR) are somnolence, headache, upper abdominal pain, fatigue, and sedation [Hirota et al 2014;Martinez-Raga et al 2015;Ruggiero et al 2014]. In the long-term prospective trials of GXR and CLON-XR the most commonly reported TEAEs are somnolence, headache, fatigue and abdominal pain [Martinez-Raga et al 2015].…”
Section: Safety and Tolerability Considerations Of Adhd Medicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…While, atomoxetine overall is less likely than stimulants to worsen sleep problems, initial somnolence can be observed, particularly if the dosage is increased too rapidly [Wolraich et al 2007]; however insomnia may also be experienced by adult patients taking atomoxetine [Wietecha et al 2013]. Likewise, the most common TEAEs associated with the α2-adrenergic receptor agonists guanfacine-XR (GXR) and clonidine-XR (CLON-XR) are somnolence, headache, upper abdominal pain, fatigue, and sedation [Hirota et al 2014;Martinez-Raga et al 2015;Ruggiero et al 2014]. In the long-term prospective trials of GXR and CLON-XR the most commonly reported TEAEs are somnolence, headache, fatigue and abdominal pain [Martinez-Raga et al 2015].…”
Section: Safety and Tolerability Considerations Of Adhd Medicationsmentioning
confidence: 99%
“…Likewise, the most common TEAEs associated with the α2-adrenergic receptor agonists guanfacine-XR (GXR) and clonidine-XR (CLON-XR) are somnolence, headache, upper abdominal pain, fatigue, and sedation [Hirota et al 2014;Martinez-Raga et al 2015;Ruggiero et al 2014]. In the long-term prospective trials of GXR and CLON-XR the most commonly reported TEAEs are somnolence, headache, fatigue and abdominal pain [Martinez-Raga et al 2015].…”
Section: Safety and Tolerability Considerations Of Adhd Medicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Guanfacine is a selective alpha 2A adrenergic receptor agonist that stimulates postsynaptic alpha 2A receptors in the prefrontal cortex (PFC), potentiating noradrenergic transmission and strengthening the connectivity of PFC networks [12,13]. This mechanism of action likely mediates the therapeutic effects of guanfacine on working memory, attention, and behavioral control [13].…”
Section: Introductionmentioning
confidence: 99%